Proceedings From an International Consensus Meeting on Posttransplantation Diabetes Mellitus: Recommendations and Future Directions. Issue 9 (6th August 2014) - Sharif, A.; Hecking, M.; de Vries, A. P. J.; Porrini, E.; Hornum, M.; Rasoul‐Rockenschaub, S.; Berlakovich, G.; Krebs, M.; Kautzky‐Willer, A.; Schernthaner, G.; Marchetti, P.; Pacini, G.; et al.
<x xml:space="preserve">Abstract</x> A consensus meeting was held in Vienna on September 8–9, 2013, to discuss diagnostic and therapeutic challenges surrounding development of diabetes mellitus after transplantation. The International Expert Panel comprised 24 transplant nephrologists, surgeons, diabetologists and clinical scientists, which met with the aim to review previous guidelines in light of emerging clinical data and research. Recommendations from the consensus discussions are provided in this article. Although the meeting was kidney‐centric, reflecting the expertise present, these recommendations are likely to be relevant to other solid organ transplant recipients. Our recommendations include: terminology revision from new‐onset diabetes after transplantation to posttransplantation diabetes mellitus (PTDM), exclusion of transient posttransplant hyperglycemia from PTDM diagnosis, expansion of screening strategies (incorporating postprandial glucose and HbA1c) and opinion‐based guidance regarding pharmacological therapy in light of recent clinical evidence. Future research in the field was discussed with the aim of establishing collaborative working groups to address unresolved questions. These recommendations are opinion‐based and intended to serve as a template for planned guidelines update, based on systematic and graded literature review, on the diagnosis and management of PTDM.